CAPITAL STRUCTURE, PROFITABILITY AND FIRM VALUE: EVIDENCE FROM MINING COMPANIES - Budianto, Diga Cendekia; Bustaman, Yosman (Academic Research Centre Services, 2016)
This research investigates the impact of firm capital structure on profitability and firm value of the twenty eight mining companies listed in Indonesia Stock Exchange from the year 2009 to 2013. The capital structure is measured by the proportion of debt over total asset, ROA and ROE are used to measure the firm profitability, meanwhile stock price is applied to measure firm value. This study uses panel data regression analysis. After controlling with external factor such as GDP rate and inflation rate, and internal factor such as revenue growth and firm size (total asset), we find leverage has negative impact on ROA however they are not significant, thus it could be said capital structure has no effect on financial performance. The indicators that significantly affect financial performance come from the control variable, which is revenue growth. Our research also finds that the capital structure has a significant effect towards firm value. The firm size and GDP rate is more impactful towards firm value. This contradicts with the MM?s capital structure irrelevance proposition, but supports other theories such as pecking order theory and Trade-off theory